2019
DOI: 10.3390/bios10010001
|View full text |Cite
|
Sign up to set email alerts
|

Complexity Measures of Voice Recordings as a Discriminative Tool for Parkinson’s Disease

Abstract: In this paper, we have investigated the differences in the voices of Parkinson’s disease (PD) and age-matched control (CO) subjects when uttering three phonemes using two complexity measures: fractal dimension (FD) and normalised mutual information (NMI). Three sustained phonetic voice recordings, /a/, /u/ and /m/, from 22 CO (mean age = 66.91) and 24 PD (mean age = 71.83) participants were analysed. FD was first computed for PD and CO voice recordings, followed by the computation of NMI between the test group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 75 publications
(100 reference statements)
1
24
0
3
Order By: Relevance
“…For subgroup analyses, as in previous research, 46 16 patients with functional independence and MoCA scores below the region‐specific cutoff 75 were classified as PD‐MCI, while 24 with preserved functional skills and normal MoCA scores were grouped as PD‐nMCI (Supporting Information Section 3). These sample sizes are similar to or larger than those of previous ML studies 13,22,57,59 . Each PD subgroup was matched to its own HC sample 44‐46 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For subgroup analyses, as in previous research, 46 16 patients with functional independence and MoCA scores below the region‐specific cutoff 75 were classified as PD‐MCI, while 24 with preserved functional skills and normal MoCA scores were grouped as PD‐nMCI (Supporting Information Section 3). These sample sizes are similar to or larger than those of previous ML studies 13,22,57,59 . Each PD subgroup was matched to its own HC sample 44‐46 .…”
Section: Methodsmentioning
confidence: 99%
“…We recruited 80 Spanish‐speaking participants (40 early‐stage PD patients with heterogeneous cognitive profiles and 40 HCs) (Table 1). This sample size meets the field's standards 13,22,23,57‐59 and equals that of dysarthria research guidelines 60 . Diagnoses were established by an expert neurologist following UK PD Society Brain Bank criteria 61 .…”
Section: Methodsmentioning
confidence: 99%
“…The recording was performed in a noise-restricted room. The de-identified data is available on RMIT website and has been reported earlier [25] .…”
Section: Methodsmentioning
confidence: 99%
“…Low HNR is an indicator of the existence of dysarthria. Studies have reported the use of other features such as the fractal dimension (FD) [25] linear predictive model (LPM) [13] , multivariate deep features [21] , and entropy [25] . Many of these studies have shown these features are very effective in differentiating between the voices of PD and healthy people.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis, including 5-s recordings of the vowel "a" and the syllable "pa", as well as text with different emotional shades in patients with Parkinson's disease and healthy people, has been described in [19]. Studies of the correlation between individual sound parameters of the voice and the severity of the condition of PD patients have also been carried out [20][21][22].…”
mentioning
confidence: 99%